2014
DOI: 10.1007/s12529-014-9404-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining Associations Between Cognitive-Affective Vulnerability and HIV Symptom Severity, Perceived Barriers to Treatment Adherence, and Viral Load Among HIV-Positive Adults

Abstract: Background Little research on symptom impairment and quality of life among HIV-positive (HIV+) individuals has attended to the potential role of cognitive-affective vulnerabilities. Emerging research indicates that emotion regulation (ER), anxiety sensitivity (AS), and distress tolerance (DT) are associated with a range of mental health outcomes and demonstrate meaningful relations to clinical outcomes in HIV+ individuals. Purpose In this investigation, we sought to concurrently examine these factors in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
(94 reference statements)
0
16
0
Order By: Relevance
“…Results indicated that anxiety sensitivity cognitive concerns predicted suicidality incrementally above and beyond the effects of demographic and health-related covariates and negative affectivity. The most recent study, conducted by Leyro et al (2015), cross-sectionally examined the predictive value of three transdiagnostic risk variables (anxiety sensitivity, emotion dysregulation, and distress tolerance) in predicting HIV symptom severity, barriers to HIV medication adherence, and viral load among 139 PLWHA (75.5% male, average age = 48.2, 42% African American). In this investigation anxiety sensitivity was shown to be significantly related to HIV symptom severity when examined concurrently with these other variables.…”
Section: Transdiagnostic Individual Difference Factorsmentioning
confidence: 99%
“…Results indicated that anxiety sensitivity cognitive concerns predicted suicidality incrementally above and beyond the effects of demographic and health-related covariates and negative affectivity. The most recent study, conducted by Leyro et al (2015), cross-sectionally examined the predictive value of three transdiagnostic risk variables (anxiety sensitivity, emotion dysregulation, and distress tolerance) in predicting HIV symptom severity, barriers to HIV medication adherence, and viral load among 139 PLWHA (75.5% male, average age = 48.2, 42% African American). In this investigation anxiety sensitivity was shown to be significantly related to HIV symptom severity when examined concurrently with these other variables.…”
Section: Transdiagnostic Individual Difference Factorsmentioning
confidence: 99%
“…One relevant factor in this area is anxiety sensitivity (AS), a cognitive vulnerability defined as the fear of anxiety, its relevant bodily sensations, and its potential negative social, physical, and mental consequences (Taylor et al, 2007). AS has unique relations to sleep disturbances and, among individuals with HIV, specifically, has been linked to greater physiological distress, anxiety, and depression symptoms (Gonzalez, Zvolensky, Parent, Grover, & Hickey, 2012; Gonzalez, Zvolensky, Solomon, & Miller, 2010), suicidality (Capron, Gonzalez, Parent, Zvolensky, & Schmidt, 2012), as well as self-reported HIV symptom severity (Leyro, Vujanovic, & Bonn-Miller, under review). …”
mentioning
confidence: 99%
“…The DERS has been used in previous studies using the HIV/AIDS population (Brandt et al, 2013; Leyro, Vujanovic, & Bonn-Miller, 2014). For the current study, internal consistency was excellent (α = 0.92).…”
Section: Methodsmentioning
confidence: 99%